Coring disturbances in IODP piston cores with implications for offshore record of volcanic events and the Missoula megafloods. (12th September 2014) - Jutzeler, Martin; White, James D. L.; Talling, Peter J.; McCanta, Molly; Morgan, Sally; Le Friant, Anne; Ishizuka, Osamu
Abstract Piston cores collected from IODP drilling platforms (and its predecessors) provide the best long‐term geological and climatic record of marine sediments worldwide. Coring disturbances affecting the original sediment texture have been recognized since the early days of coring and include deformation resulting from shear of sediment against the core barrel, basal flow‐in due to partial stroke, loss of stratigraphy, fall‐in, sediment loss through core catchers, and structures formed during core recovery and on‐deck transport. The most severe disturbances occur in noncohesive (sandy) facies, which are particularly common in volcanogenic environments and submarine fans. Although all of these types of coring disturbances have been recognized previously, our contribution is novel because it provides an easily accessible summary of methods for their identification. This contribution gives two specific examples on the importance of these coring disturbances. We show how suck‐in of sediments during coring artificially created very thick volcaniclastic sand layers in cores offshore Montserrat and Martinique (Lesser Antilles). We then analyze very thick, structureless sand layers from the Escanaba Trough inferred to be a record of the Missoula megafloods. These sand layers tend to coincide with the base of core sections, and their facies suggest coring disturbance by basal flow‐in, destroying the original structure and texture of the beds. We conclude by outlining and supporting IODP‐led initiatives to further reduce and identify coring disturbances and acknowledge their recent successes in drilling challenging sand‐rich settings, such as during IODP Expedition 340.